Self, Identity, and Collective Action - Tremblay, Francine (Lexington Books, 2023)
Based on the work of George Herbert Mead, Han Joas, and Axel Honneth, as well as the author’s own personal and academic identities and journeys, Self, Identity, and Collective Action argues that the self and action are strictly related. Reading these authors provided Francine Tremblay with the theoretical ground to stand on while thinking about identity and how it is linked to civic participation. She posits that Mead’s work and its link to action must be revisited and given its rightful place in sociology, and thatsociology must be radical, committed, and passionate.